Typification of the names Michelia cathcartii and Magnolia gustavii (Magnoliaceae) - Kumar, Anand; Bharati, Kumar Avinash (Phytotaxa, 2020)
The genus Magnolia Linnaeus (1753: 398) is represented by ca. 219 species, distributed in Himalaya to Japan & West Malesia and north-eastern America to tropical America (Mabberley 2017). In India, it is represented by 25 species (Raju 1993, Kundu 2009, POWO 2019), out of which two species [M. punduana (Hooker & Thomson 1855: 81) Figlar (2000: 23) and M. pleiocarpa (Dandy 1933: 313) Figlar & Nooteboom (2004: 95)] are endemic to India (Singh et al. 2015).